2018
DOI: 10.1038/s41598-017-19114-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficient differentiation of human pluripotent stem cells into skeletal muscle cells by combining RNA-based MYOD1-expression and POU5F1-silencing

Abstract: Direct generation of skeletal muscle cells from human pluripotent stem cells (hPSCs) would be beneficial for drug testing, drug discovery, and disease modelling in vitro. Here we show a rapid and robust method to induce myogenic differentiation of hPSCs by introducing mRNA encoding MYOD1 together with siRNA-mediated knockdown of POU5F1 (also known as OCT4 or OCT3/4). This integration-free approach generates functional skeletal myotubes with sarcomere-like structure and a fusion capacity in several days. The PO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Our strategy uses syn-mRNAs encoding for TFs (syn-TFs) for the forced expression of TFs. As we have also shown in our earlier work 1720,59 , syn-TF-based differentiation of hPSCs is footprint-free, because mRNAs are directly translated into proteins to function and are not converted into DNAs, which could cause unfavorable genome modification 60 . The forced expression of combinations of TFs directly manipulates the gene regulatory network, which is most likely the reason for the faster and more efficient differentiation of hPSCs into NPCs and kidney cells compared to growth factor- and small molecule-based methods.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Our strategy uses syn-mRNAs encoding for TFs (syn-TFs) for the forced expression of TFs. As we have also shown in our earlier work 1720,59 , syn-TF-based differentiation of hPSCs is footprint-free, because mRNAs are directly translated into proteins to function and are not converted into DNAs, which could cause unfavorable genome modification 60 . The forced expression of combinations of TFs directly manipulates the gene regulatory network, which is most likely the reason for the faster and more efficient differentiation of hPSCs into NPCs and kidney cells compared to growth factor- and small molecule-based methods.…”
Section: Discussionmentioning
confidence: 55%
“…In a previous study, we demonstrated that silencing POU5F1 (also known as OCT4, OCT3/4) accelerated MYOD1-mediated myogenic differentiation of hPSCs 17 . To test whether suppressing POU5F1 expression is also beneficial for kidney differentiation, we transfected siRNA targeting POU5F1 (siPOU5F1) with syn-HNF1A and determined the efficiency of differentiation.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In previous studies by others, more than 2 weeks were necessary just to induce PDX1 + /NKX6.1 + cells. We have previously reported differentiation methods for neurons [ 13 ], skeletal muscle cells [ 17 ], and lacrimal gland epithelium-like cells [ 15 ] in a short period of time by introducing synthetic mRNAs encoding specific transcription factors required for the target mature cells. In this study, we have attempted to shorten the period of time required for the induction of pancreatic endocrine cells from human pluripotent stem cells with the same differentiation method using PDX1 and NKX6.1 synthetic mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation by synRNAs holds many desirable features for further clinical application, because it allows rapid, efficient, and footprint-free differentiation of human pluripotent stem cells [ 16 ]. We have also reported that the forced silencing of pluripotency master regulator POU5F1 (also known as OCT4, OCT3/4) by siPOU5F1 facilitates synRNA-based hPSC differentiation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%